2020
DOI: 10.1094/mpmi-05-20-0109-a
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome Profiling Data ofBotrytis cinereaInfection on Whole PlantSolanum lycopersicum

Abstract: Botrytis cinerea is a foliar necrotrophic fungal-pathogen capable of infecting >580 genera of plants, is often used as model organism for studying fungal-host interactions. We used RNAseq to study transcriptome of B. cinerea infection on a major (worldwide) vegetable crop, tomato (Solanum lycopersicum). Value to the scientific community. Most previous works explored only few infection stages, using RNA extracted from entire leaf-organ diluting the expression of studied infected region. Many studied B. ciner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Transcriptional profiling during the B. cinerea infection process has been performed in several angiosperms [38][39][40][48][49][50][51]. However, no information related to the molecular mechanisms used by B. cinerea during moss invasion is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional profiling during the B. cinerea infection process has been performed in several angiosperms [38][39][40][48][49][50][51]. However, no information related to the molecular mechanisms used by B. cinerea during moss invasion is available.…”
Section: Discussionmentioning
confidence: 99%
“…All primer combinations showed amplification efficiencies greater than 95%. [38], Lactuca sativa (lettuce) [39], and Solanum lycopersicum (tomato) [40], were obtained from NCBI. These plant hosts were chosen since A. thaliana represents a model plant for angiosperms, and S. lycopersicum and L. sativa are two important crops affected by B. cinerea.…”
Section: Rna Extraction Rna Sequencing Data Processing and Qpcr Anamentioning
confidence: 99%
“…The Botrytis cinerea transcriptome in planta was addressed in a few species, such as A. thaliana 6 , cucumber [ 21 ], kiwifruit [ 22 ], tomato, and others [ 23 ]. However, the molecular mechanisms associated with successful B. cinerea infection during the early stages of fruit ripening are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been trying to clarify the transcriptome landscape behind B. cinerea virulence in different species, such as cucumber and A. thaliana leaves [ 6 , 21 ], kiwifruit [ 22 ], tomato fruit, and others [ 23 ]. Moreover, the fungus transcriptome during infection of grapes (cv.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that during the fungal infection process, several transcriptome changes take place, especially in the genes coding secreted proteins involved in pathogenesis [6][7][8]. In order to monitor changes in the gene expression during pathogenesis in a sensitive and specific manner, reverse transcription quantitative polymerase chain reaction (RT-qPCR) can be used.…”
Section: Introductionmentioning
confidence: 99%